DIPLOMASI INDONESIA DALAM MENDUKUNG PALESTINA MENJADI NEGARA PENINJUA DI PBB TAHUN 2012 - Saibatul Aslamiah; Ahmad Jamaan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research aims to describe the efforts of Indonesia to support Palestinian struggle to increase its status in the United Nation. After failed to become a UN member states in 2012, Palestine seeked non-member observer state status for Palestine on the basis of Palestine’s pre-1967 borders 29 November 2012. Indonesia as a UN member state and also has a close relation with Palestine was played a role in supporting it. Authors applied multilateral diplomacy from G. R. Berridge and Sumaryo Suryokusumo to describe Indonesian government diplomacy toward another UN mamber states in the United Nations General Assembly proses. Authors also used multitrack diplomacy from Dr. Luoise Diamond and John McDonald to describe another Indonesian efforts to support Palestine independecy. This reseacrh shows that Indonesia played a significant role in supporting Palestine to collect internasional recognation to its independecy. Throughout multilateral diplomacy proses in the United Nations General Assembly, Indonesian governtment took all the possible role to support Palestine application to become a non-member observer state, by became a co-sponsor for the application, came to the assembly, gave supporting speech at the debate session and vote to support the application. In another way Indonesian people have done many kinds off support for Palestine that authors explain by using multitrack diplomacy. Keywords: multilateral diplomacy, non-member observer state, Palestine, United Nation, sovereignity.